PERAN IMPLEMENTASI GREEN BANKING PADA BANK SYARIAH INDONESIA - Lelawati, Nina; Darmayanti, Elmira Febri; Nusantoro, Jawoto (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Banking that prioritizes social and environmental finance and the preservation of natural resources is known as